COMORBID COURSE OF ALLERGIC RHINITIS WITH BRONCHIAL ASTHMA IN CHILDREN (Proceedings of International Educators Conference, 2023)
In this article, the diagnosis of allergic rhinitis in children with bronchial asthma comorbidity, using a specially developed questionnaire, based on allergy anamnesis was considered. A retrospective study was conducted included 82 patients aged 2-13 years. From the medical history and outpatient map studied demographic characteristics: age, gender, place of residence, clinical characteristics: duration of disease, severity of AR and course of AR according to the classification of ARIA, 2018 ( Allergic Rhinitis and Impaction Asthma), concomitant allergic diseases the severity of bronchial asthma was determined according to the classification of GINA, 2016.